Analisis Efek Merger Bank Bumn Syariah Di Bursa Efek Indonesia - Chairul Ihsan Burhanuddin; Amran Amran (AkMen JURNAL ILMIAH, 2021)
In the midst of uncertain economic conditions in various countries around the world, it requires every country to innovate and improvise in maintaining all aspects to survive. Due to this problem, one form of innovation carried out by the Indonesian government, especially in stock trading, was the merger of a Sharia bank. The merger process of three Islamic banks (BRI Syariah, BNI Syariah, and Mandiri Syariah) to become Bank Syariah Indonesia (BSI) with the BRIS code on the Indonesia Stock Exchange has provided positive sentiment, literacy and understanding to the public in investing in the stock exchange. This research is a qualitative descriptive study. The results of this study indicate that one of these merger processes provides positive sentiment in various aspects of stock trading on the stock exchange. Starting from stock trading activities and the portion of investor ownership which is dominated by local investors